Use of Discretion in Criminal Acts by the Police in Hart's View - Samsul Rijal Sahir (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research discusses that the application of discretion often causes problems. However, on the one hand, discretion is also helpful for the Police in carrying out the investigation and investigation process so that they can quickly solve a problem that arises in the field. Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia was born to try to put discretion into the practice of criminal law. The Criminal Procedure Code describes how discretion is applied, but the measure of the application of discretion, whether this discretion is better to exist or not, the value of discretion applied in Indonesia, and how we can exercise discretion. It has yet to be answered, and it is often a problem in the field because it seems arbitrary; for this reason, it is necessary to revise Law Number 2 of 2002 concerning the Police, which explains what discretion is and how it is applied. The research method used is normative legal research, which traces the legal literature linked to the discretionary concept approach presented by Hart.